Peternakan Eduwisata Kambing-Domba Pentahelix dalam Mendukung Ketahanan Protein di Sumatera Utara - Yunilas, Yunilas; Siregar, Ameilia Zuliyanti; Tulus; Rahmadini, Salsabila; Nasution, Muheri Indra Aja (PASAI : Jurnal Pengabdian kepada Masyarakat, 2023)
Arjuna Farm is a goat-sheep farm that was established to increase family income with an educational concept that targets meeting the community's protein needs. Limited knowledge in the field of animal husbandry in the form of procurement of feed ingredients, ration formulation, and management, encouraged the team from the LPPM Annual Service, Universitas Sumatera Utara to provide assistance with solutions offered to farmers, including providing training, lectures, discussions, and demonstrations of waste-based feed processing. agriculture, and food processing industry, making complete silage feed, making MOL bio activator in fermentation and maintenance management. This activity is expected to increase the knowledge and skills of breeders. Apart from that, assistance was provided in the form of goat milking equipment and cage design. This activity is predicted to result in savings in animal feed costs because it can utilize alternative sources of feed ingredients, formulate and make concentrate feed independently, and complete fermentation methods.